The effects of positive versus negative impact reflection on change in job performance and work-life conflict - Cardador, M. Teresa (Frontiers in Psychology, 2014)
Research on task significance and relational job design suggests that information from beneficiaries of one’s work fosters perceptions of impact, and thus improved work outcomes. This paper presents results from a longitudinal field experiment examining the effect of another strategy for fostering perceptions of impact – engaging employees in regular reflection about how their work benefits others. With a sample of professionals from multiple organizations, this longitudinal study examined the effect on job performance and work-life conflict of both positive and negative impact reflection. Results show that negative impact reflection had a pronounced negative effect on job performance, but no effect on work-life conflict. Positive impact reflection had a weak positive effect on work-life conflict, but no significant effect on job performance. The direction of effects seen in the no intervention condition mirrored that of the negative impact reflection condition, suggesting a possible buffering effect for positive impact reflection. This research provides empirical and theoretical contributions to the literatures on relational job design and task significance.